An Overview of Emerging Analytics in Big Data: In-Situ - Sultana, Mehjabeen (International Journal of Computer Sciences and Engineering, 2025)
Conventional simulation techniques generate massive amounts of data that are analyzed using various applications. These simulations produce petabytes of data that strains the I/O and storage subsystem. To overcome the high latency in I/O operations, data is analyzed as it is generated, in-situ. This can be successfully achieved by enabling analysis techniques on the same HPC machine that is producing simulation by using the same hardware resources or on a separate analysis machine. In this research paper, we discuss state of the art techniques in this domain and support our conclusion by comparing pros and cons of each approach.